2021
DOI: 10.3389/fimmu.2021.607178
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Using Muramyl Peptides - Modulators of Innate Immunity of Bacterial Origin - in Medicine

Abstract: The spread of infectious diseases is rampant. The emergence of new infections, the irrational use of antibiotics in medicine and their widespread use in agriculture contribute to the emergence of microorganisms that are resistant to antimicrobial drugs. By 2050, mortality from antibiotic-resistant strains of bacteria is projected to increase up to 10 million people per year, which will exceed mortality from cancer. Mutations in bacteria and viruses are occurring faster than new drugs and vaccines are being int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 102 publications
1
28
0
1
Order By: Relevance
“…A similar decrease in IgE with the advance administration of LPS and GMDP prior to antigen sensitization explains the positive effect of the treatment of asthma and atopic diseases using GMDP, obtained in clinical practice [57][58][59]. Asthma is known to be caused primarily by the binding of complexes of the allergen and allergen-specific IgE to their receptors on antigen-presenting cells and the presentation of the processed allergen to T cells.…”
Section: Discussionmentioning
confidence: 86%
“…A similar decrease in IgE with the advance administration of LPS and GMDP prior to antigen sensitization explains the positive effect of the treatment of asthma and atopic diseases using GMDP, obtained in clinical practice [57][58][59]. Asthma is known to be caused primarily by the binding of complexes of the allergen and allergen-specific IgE to their receptors on antigen-presenting cells and the presentation of the processed allergen to T cells.…”
Section: Discussionmentioning
confidence: 86%
“…GO enrichment analysis suggested that it was significantly enriched in the “response to LPS” and “response to bacterial molecular sources”. Cytowall peptides, as a known component of peptidoglycan, can participate in hematopoietic processes and stimulate the production of colony-stimulating factors for the treatment of tumor cells [ 25 ]. At the same time, LPS functions as a major component of the cell wall of Gram-negative bacteria, which can be recognized by TLR-4 and alter the immune response in different cancer patients [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Defensin secretion is induced both by whole bacteria and by their components, for example, by LPS, lipoteichoic acid, lipid A, and muramyl peptides [ 115 , 116 , 117 ]. After it was shown that CpG oligodeoxynucleotides also induce the secretion of defensins, it became obvious that stimulation of the TLR or NLR receptors of the innate response is the signal for the release of defensins by cells [ 118 , 119 , 120 ].…”
Section: Immunomodulatory Activity Of Ampsmentioning
confidence: 99%